A NOTE ON PRINCIPLES OF ACCOUNTING. - Nelson, Edward G. (The Accounting Review, 1939)
The authors of "Tentative Statement of Accounting Principles" have accomplished something for which the accounting profession, teachers and practitioners alike, should be grateful. They have described carefully and concisely what accountants do and their "statement" indicates the nature of current "good accounting practice." They have not attempted to prepare a text for those who have no knowledge of fundamentals, for such texts exist in ample number. As was to be expected, the results of this effort did not meet with universal approval. Accounting, as author A.C. Littleton declares, is "...relative and progressive. The phenomena which form its subject matter are constantly changing. Older methods become less effective under altered conditions: earlier ideas become irrelevant in the face of new problems." Professional accord seldom occurs in such fields of knowledge. Fortunately much of the recorded disharmony is more apparent than real: Disagreements frequently arise when conclusions are stated without reference to premises. The evolution of accounting practice sometimes, in fact usually, proceeds more rapidly than the statement of postulates. It is therefore intended, in this paper, to indicate how some of the grounds for discord will disappear when the premises of an accounting and a theory of business enterprise are made explicit, and to suggest that some of the work by the committee for revision should be concerned with a statement of premises and a theory.